PERAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR. PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI (Studi Pada Minist?rio Da Solidariedade Social) - B. Florindo, Lelia Paula Da Rosa; Sintaasih, Desak Ketut; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
This study aimed to analyze the mediating role of organizational citizenship behavior in the effect of transformational leadership and work motivation on employee performance at the Minist?rio Da Solidariedade Social. This study was conducted with the involvement of all employees as respondents in the Head Office of Minist?rio Da Solidariedade Social, are 75 employees. Data were collected by distributing questionnaires. Furthermore, the data that has been collected analyzed by using SmartPLS 2.0 M3.           The result of analysis showed that transformational leadership and motivation are significant positive effect on employee performance. Transformational leadership and motivation are significant positive effect on organizational citizenship behavior. Organizational citizenship behavior is significant positive effect on employee performance. However, organizational citizenship behavior is an partial mediation on the effect of transformational leadership and work motivation to employee performance.
Keywords: transformational leadership, work motivation, OCB, and employee performance